Pengaruh CAR, NPF, FDR, dan OER, Terhadap ROA Pada Bank Pembiayaan Rakyat Syariah di Indonesia Periode Januari 2009 Hingga Mei 2014 - Linda Widyaningrum; Dina Fitrisia Septiarini (Universitas Airlangga, 2015)
Islamic Rural Bank is intermediary institution that collect and distribute the fund in financing. BPRS management hope that every operational activities always shows good performance in order to obtain optimal benefit. One of the way to measure performance is calculating financial ratios. The purpose of this research to know the effect of CAR, NPF, FDR, and OER on ROA in industry of Islamic Rural Bank period January 2009 until May 2014 in partial and simultaneous. This research method used quantitative approach. Sample of this research was based on monthly period, so there were 65 months/samples. Sampling technique used purposive sampling. All data taken from Sharia Islamic Statistic. Analyze technique used multiple regression.The results of this research showed that in simultaneous, CAR, NPF, FDR, and OER had significant effect on ROA. In partial, CAR, NPF, and FDR had not significant effect on ROA, beside OER had significant effect on ROA.